Pediatric Sports-Related Concussion: An Approach to Care. Issue 4 (July 2022) - Podolak, Olivia E.; Arbogast, Kristy B.; Master, Christina L.; Sleet, David; Grady, Matthew F.
Sports-related concussion (SRC) is a common sports injury in children and adolescents. With the vast amount of youth sports participation, an increase in awareness of concussion and evidence that the injury can lead to consequences for school, sports and overall quality of life, it has become increasingly important to properly diagnose and manage concussion. SRC in the student athlete is a unique and complex injury, and it is important to highlight the differences in the management of child and adolescent concussion compared with adults. This review focuses on the importance of developing a multimodal systematic approach to diagnosing and managing pediatric sports-related concussion, from the sidelines through recovery.